Analysis of the Effect of Community Perceptions and Demographic Factors on the Behavior of the Covid-19 Booster Vaccination at the Telaga Murni Health Center, Bekasi Regency - Fitriyah, Fitriyah; Tahun, Omega DR (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Vaccination against Covid-19 in Indonesia has not gone well, many respondents do not believe that Covid-19 (SARS-CoV-2) is real or has the possibility to spread and threaten public health. Several respondents stated that the pandemic was a product of propaganda, conspiracy, hoax, and/or a deliberate attempt to spread fear through the media for profit. Many of the people are not willing to receive booster vaccines, various reasons arise and result in vaccination achievements not reaching the target. The purpose of this study was to determine the influence of public perceptions and demographic factors on booster vaccine behavior. This research was conducted at the Telaga Murni Health Center, Bekasi Regency in 2022. This type of research is a quantitative analytical survey with a cross-sectional study approach, the type of statistical test used is the Chi Square test. And the population in this study were all patients visiting the puskesmas, the sample being 85 respondents. Sample selection technique by means of Systematic Random Sampling. The results of statistical tests showed that the factors that influenced people's behavior in administering booster vaccines were: perception (p value=0.007), age (p value=0.026), and level of education (p value=0.003). While the variables that have no effect are gender (p value = 0.307) and occupation (p value = 1.0).